Biodiversity Flashcard: Inovasi Media Pembelajaran IPA Sub Materi Keanekaragaman Hayati dan Konservasi Kelas VII - Tapilouw, Marisa Christina; Trisianna, Jessica Ayu; Sucahyo, Sucahyo (Faculty of Teaching and Education, University of Wiraraja, 2025)
Development in the education world become a challenge for teachers in doing learning innovation, especially in science learning on Biodiversity and Conservation. The objectives of the study were (1) developed flashcard learning media; (2) analyzed the effectiveness of science learning on Biodiversity and Conservation using flashcard media. This study use Research and Development (R&D) method with ADDIE model (Analyze, Design, Develop, Implementation, and Evaluation). In Analyze stage, teachers had never applied flashcard media to Biodiversity and Conservation materials. In Design Stage, Biodiversity Flashcard was designed. In Develop stage, 84% of flashcard media validation material aspects and 87% of media aspects were classified as